2021
DOI: 10.21037/tau-20-914
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin 6 and acute urinary retention in elderly men with benign prostatic hyperplasia in China: a cross-sectional study

Abstract: Background: While acute urinary retention (AUR) is a severe complication of benign prostatic hyperplasia (BPH), it can also indicate the progression of this common disease in aging men. This study aimed at exploring the possible relationship between serum interleukin 6 (sIL-6) and AUR in BPH patients. Methods: A cross-sectional study was conducted based on 256 elderly men with BPH in China. The association between the sIL-6 level and the occurrence of AUR was evaluated by univariate and multivariable logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Cross-sectional studies of sIL-6 and sIL-8 in 256 and 245 BPH patients were conducted using univariate and multivariate logistic regression analyses. The results revealed a positive correlation between sIL-6 and sIL-8 levels in the AUR group and AUR [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies of sIL-6 and sIL-8 in 256 and 245 BPH patients were conducted using univariate and multivariate logistic regression analyses. The results revealed a positive correlation between sIL-6 and sIL-8 levels in the AUR group and AUR [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a previous study has highlighted that the risk of urinary retention is tightly associated with inflammation [ 17 ]. Wu et al [ 18 ] have exhibited that the serum concentration of IL-6 was notably enhanced in patients with acute urinary retention. Our ELISA results revealed that Prostant treatment notably diminished the serum level of proinflammatory cytokines including TNF- α and IL-6 both on the first and second day after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al reported in their cross-sectional studies that high sIL-6 and sIL-8 levels in BPH patients were considered to be significantly correlated with acute urinary retention (OR = 9.67/ 8.85). 52,53 Smith et al reported that IL-8 and its receptors directly promoted the growth of prostate epithelial cells through the IL-8 axis in BPH patients. 54 Arivazhagan et al reported that serum IL-17, which is a T-lymphocyte-derived proinflammatory cytokine, levels in BPH patients were significantly higher than those of a normal control group.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Wu et al. reported in their cross‐sectional studies that high sIL‐6 and sIL‐8 levels in BPH patients were considered to be significantly correlated with acute urinary retention (OR = 9.67/8.85) 52,53 . Smith et al.…”
Section: Intrinsic Factorsmentioning
confidence: 99%